The Roles of H2O/Tetrahydrofuran System in Lignocellulose Valorization - Li, Jianmei; Zhang, Wenyu; Xu, Shuguang; Hu, Changwei (Frontiers in Chemistry, 2020)
Conversion of lignocellulosic biomass to fuels and chemicals has attracted considerable attention around the world, while lowering the recalcitrance of lignocellulosic biomass in a cost-effective manner is still challenging to commercialize biomass-based technologies. Solvent system plays the important role in the pretreatment of lignocellulose as well as the selective formation of target products. In particular, H2O/tetrahydrofuran (H2O/THF) system has recently been widely applied in lignocellulose valorization, which is proved to exhibit outstanding efficiency for solubilization-conversion lignocellulose, solubilization of the intermediates and products, and shifting reaction equilibrium, thereby significantly improving the yield, selectivity of target products, as well as the full utilization of lignocellulose. In addition, THF shows low toxicity, and is considered as a renewable solvent as it can be manufactured from bio-derived chemicals. Herein, this review concentrates on the advances of H2O/THF system in lignocellulose valorization in recent years. Several aspects relative to the roles of H2O/THF system are descripted as follows: the pretreatment of lignin, solubilization-conversion of hemicellulose and cellulose components in lignocelluloses, and the promoting formation of valuable chemicals like furfural, 5-hydroxymethyl furfural (HMF), levulinic acid and so on, as well as the inhibiting role in humins formation. This review might provide useful information for the design of effective solvent systems in full utilization of lignocellulosic biomass.